Race in modern Irish literature and culture - Brannigan, John (Edinburgh University Press, 2009)
For decades Ireland presented itself as the land of hospitality, until the 1990s, when the 'Celtic Tiger' exposed its racist underbelly. In Race in Modern Irish Literature and Culture, John Brannigan argues that race and racism have longer histories in the Irish state, histories which have often been exposed and critiqued by Irish writers and artists. He revisits the role of racial ideologies in the foundation and development of the state, offering original historical insights, and inspired new readings of literary and cultural works ranging from Ulysses to The Commitments. Key Features Provides new research on the social history of racial ideologies and racist expressions in the Irish state since 1922 Offers new readings of Irish cultural productions and literary texts (by James Joyce, W.B. Yeats, Samuel Beckett, Liam O'Flaherty, Kate O'Brien, Edna O'Brien, Brendan Behan, James Plunkett, Paul Durcan, Austin Clarke, Aidan Higgins, Denis Johnston, and others) emphasising how they engage with the histories of Irish racism and raciology Demonstrates how a new understanding of the constitutive role of race and racism in modern Irish culture might necessitate a revision of the dominant precepts and trends in contemporary Irish studies Addresses the significance of the social and cultural history of race and racism in twentieth-century Ireland for the post-'Celtic Tiger' era